Peran Shopping Enjoyment Memediasi Pengaruh Store Atmosphere Terhadap Impulse Buying - Dwikayana, I Made Brahmanta; Widagda K, I Gusti Ngurah Jaya Agung (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
This study aims to explain how shopping enjoyment acts as a mediator in the relationship between store atmosphere and impulse buying among consumers at Mall Living World, Denpasar. The research population consists of all consumers who have made impulse purchases at the mall. The sample comprises 120 consumers selected through purposive sampling. Data analysis was conducted using Path Analysis within the SEM-PLS framework. The results indicate that store atmosphere has a positive and significant effect on impulse buying (coefficient = 0.398; t-statistic = 4.093; p < 0.001) and shopping enjoyment (coefficient = 0.756; t-statistic = 18.785; p < 0.001). Shopping enjoyment also positively and significantly influences impulse buying (coefficient = 0.466; t-statistic = 4.749; p < 0.001). Furthermore, shopping enjoyment partially mediates the relationship between store atmosphere and impulse buying, with a mediation effect of 0.352 (t-statistic = 4.578; p < 0.001). These findings confirm that enhancing the store atmosphere can increase shopping enjoyment, ultimately driving consumers’ impulse buying behavior. The implications for the management of Mall Living World, Denpasar, highlight the importance of continuously developing an attractive store atmosphere to create a pleasant shopping experience and boost the potential for impulse purchases.